Physiological effects of sulfadiazine and sulfamethoxazole on Skeletonema costatum and toxicological evaluation using IBRv2 index - Yurong Zhang; Tiejun Li; Yuxin Lin; Dongdong Xu; Haifeng Jiao (Ecotoxicology and Environmental Safety)
Sulfonamide antibiotics, widely used in human and veterinary medicine as well as agriculture, pose environmental concerns due to their stability and poor biodegradability. This study fills a critical gap in understanding the ecological impact of sulfonamide antibiotics on marine microalgae, particularly Skeletonema costatum, a key primary producer in marine ecosystems. This study investigated the biological responses of the marine microalga Skeletonema costatum to sulfadiazine (SD) and sulfamethoxazole (SMX). Both antibiotics significantly impacted S. costatum, with SD having a more pronounced effect. Growth studies showed a clear dose-response relationship: Low concentrations (0.5 mg/L) of SD and SMX stimulated growth, while higher concentrations (3 mg/L, 5 mg/L, and 10 mg/L) inhibited growth. The 96-hour half-maximal inhibitory concentrations (96h-IC50) were 1.654 mg/L and 1.838 mg/L, respectively, initially indicating that SD has a stronger inhibitory effect on S. costatum than SMX. Photosynthetic activity, measured by chlorophyll a content and the maximum quantum yield of photosystem II (Fv/Fm) values, showed that low concentrations (0.5 mg/L) of SD and SMX increased photosynthetic efficiency, while high concentrations (3 mg/L, 5 mg/L, and 10 mg/L) significantly inhibited it. Antioxidants activity analysis revealed that SD and SMX exposure altered superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), glutathione reductase (GR), and malondialdehyde (MDA) levels. SOD, GR, and GSH-Px levels initially increased but later decreased, suggesting a synergistic effect, while MDA levels consistently increased, indicating oxidative stress and biochemical disruption in algal cells. The Integrated Biomarker Response Version 2 (IBRv2) index provided a comprehensive evaluation of the ecological risks posed by SD and SMX, demonstrating that these antibiotics can significantly disrupt the physiology of marine microalgae. The IBRv2 index provided a comprehensive evaluation of the ecological risks posed by SD and SMX, demonstrating that these antibiotics can significantly disrupt the physiology of marine microalgae. Higher IBRv2 values for SD exposure indicated more substantial impacts on S. costatum. This study underscores the significant ecological risks of sulfonamide antibiotics in marine environments, highlighting the need for further research and regulation to mitigate their impact.